STUDI KORELASI LAND SUBSIDENCE DENGAN INTRUSI AIR LAUT DI WILAYAH PESISIR SEMARANG DAN DEMAK - Yesinta Lailatul Alfissa, Nur
Semarang and Demak are the district located at the north coast of Central Java, which industrial areas are thriving and overcrowded. This has caused the industry and residents take excessive of groundwater to support the activity. Excessive of groundwater extraction continuously, could cause negative effects such as land subsidence and seawater intrusion. Based on the factor of excessive of groundwater extraction, there is an indication of a correlation of land subsidence with seawater intrusion, mainly in the coastal areas. For that, the authors observed several bore wells in the area affected by land subsidence and unaffected areas land subsidence. Then, the bore wells sample data are overlayed with land subsidence data as secondary and calcute quantitatively using grid. The aims to determine the spatial relationship of land subsidence with seawater intrusion whether it correlates positive or negative and to understand the affected area by land subsidence and seawater intrusion. The results have shown that the total area affected by the land subsidence in Semarang and Demak area is 93751.6986 Ha while seawater intrusion area is 56613.3290 Ha and 56138.3290 Ha for area affected by land subsidence and seawater intrusion. Based on spatial analysis, the sample of seawater intrusion in the land subsidence area where the seawater intrusion boundary occurred at 99 cm land subsidence magnitude while the distance of seawater intrusion has reached 14 km perpendicular to coastline until the Guntur District. This shows a positive correlation which is the pattern of land subsidence show a pattern of seawater intrusion that is inseparable from the factor of groundwater extraction, land use and geological conditions of the region.